Evaluation of BDS-2 real-time orbit and clock corrections from four IGS analysis centers. (15th January 2021) - Ouyang, Chenhao; Shi, Junbo; Huang, Yongshuai; Guo, Jiming; Xu, Chaoqian
Highlights: All available BDS real-time orbit and clock correction resources including WHU, DLR, GFZ, and CNE are investigated. BDS real-time orbit accuracies and clock precisions of four IGS ACs are assessed. BDS real-time PPP performances based on various real-time products are evaluated in both static and kinematic modes. Real-time orbit/clock correction usage recommendations are provided for BDS real-time PPP users. Abstract: Real-time precise orbit/clock product is fundamental to BeiDou Navigation Satellite System (BDS) real-time precise point positioning (PPP). In order to explore achievable performance of BDS real-time orbit/clock products and thus offer usage recommendations for BDS real-time PPP users, this paper studies BDS real-time orbit/clock corrections provided by four International GNSS Service (IGS) Analysis Centers (ACs), i.e. Wuhan University (WHU), Deutsches Zentrum für Luft- und Raumfahrt (DLR), GeoForschungsZentrum Potsdam (GFZ) and Centre National d' Etudes Spatiales (CNE) for seven consecutive days staring from day of year (DOY) 324, 2019. Firstly, the availability of BDS-2 real-time orbit/clock corrections is studied. Larger than 85% availabilities are identified for all ACs. During the test period, DLR does not provide all Geosynchronous Earth Orbit (GEO) satellites' corrections, whereas CNE does not provide C14/C16′s corrections. Secondly, the BDS real-time orbit accuracy is analyzed. Results indicate that the real-time orbit accuracy of GEO satellites is at meter level, and those of Inclined Geosynchronous Satellite Orbit (IGSO)/Medium Earth Orbit (MEO) satellites are at decimeter level. Among all ACs, the accuracy of CNE's three-dimensional (3D) orbit correction is the best, which is 2.391/0.278/0.271 m for GEO/IGSO/MEO satellites, respectively. DLR has the largest orbit errors of 1.116/0.504 m for IGSO/MEO satellites. Thirdly, the BDS real-time clock offset precision is investigated. On the one hand, CNE's real-time corrections still perform best with 1.19/0.28/0.32 ns clock offset precision for GEO/IGSO/MEO satellites, respectively. On the other hand, DLR's real-time clock is the worst with 2.61/1.91 ns IGSO/MEO clock offset precision. Finally, all corrections are applied to estimate 47 Multi-GNSS Experiment (MGEX) station's BDS-2 real-time PPP on DOY 330, 2019. Results show an average of 0.53–1.46 h convergence time and 8.8–10.9 cm positioning accuracy in the static mode. In the meantime, the average convergence time in the kinematic mode is 2.11–9.84 h, much longer than the static counterpart. The corresponding converged positioning accuracy is 30.7–68.0 cm. To sum up, WHU/GFZ/CNE's real-time corrections are proven with satisfied orbit/clock performance, thus are recommended for BDS-2 real-time PPP.